Pelatihan Pengolahan dan Diversifikasi Produk Aren untuk Pemberdayaan UMKM Desa Sukaharja Kabupaten Tasikmalaya - Hidayat, Cepi Rahmat; Nurani, Riga Zahara; Rahayu, Intan; Dwiyanti, Hidayah; Setyawardani, Triana; Ardiansyah, Ardiansyah (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the capacity and skills of Silih Asih MSME actors in Sukaharja Village, Tasikmalaya Regency, in producing premium-quality palm sugar products and developing value-added product innovations. The program was implemented through training and mentoring activities involving 20 participants. Evaluation instruments included written tests (pre-test and post-test), skill observation sheets, and participant response questionnaires. Data were analyzed using descriptive quantitative methods by comparing participants’ average pre-test and post-test scores to assess overall competency improvement. The results indicate a significant increase in participants’ competencies, with the average pre-test score improving from 58 to 88 in the post-test. In addition to enhanced technical skills, participants also gained a better understanding of the importance of quality standards and attractive packaging design. These findings demonstrate that the program is effective in fostering self-reliance and enhancing the competitiveness of MSMEs based on local potential.